2023
DOI: 10.1002/nau.25155
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after total excision of transobturator tape inserted for treatment of stress urinary incontinence

Abstract: Introduction: Midurethral tapes (MUTs) were the most common surgical treatment for stress urinary incontinence (SUI) between 2008 and 2017.Transobturator tapes were introduced as a novel way to insert MUTs. Some women have experienced life-changing complications, and opt to undergo a total excision of transobturator tape (TETOT). There is a paucity in evidence about the outcomes of TETOT, which is a complex operation. This study aims to report clinical outcomes of all women who underwent TETOT in a specialist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Evidence on the outcomes of SRS is continuously growing as studies focusing on this subject have been reported recently. However, most published studies have been too heterogenous, usually consisting of female patients with every kind of mesh‐related complication 3,4,9,10,23 . It is logical to perform total mesh removal in patients with pain, infectious exposure and extrusion complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the outcomes of SRS is continuously growing as studies focusing on this subject have been reported recently. However, most published studies have been too heterogenous, usually consisting of female patients with every kind of mesh‐related complication 3,4,9,10,23 . It is logical to perform total mesh removal in patients with pain, infectious exposure and extrusion complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, most published studies have been too heterogenous, usually consisting of female patients with every kind of mesh‐related complication. 3 , 4 , 9 , 10 , 23 It is logical to perform total mesh removal in patients with pain, infectious exposure and extrusion complications. On the other hand, total mesh removal is a complex and time‐consuming surgery and usually not being used for female patients with MRUO.…”
Section: Discussionmentioning
confidence: 99%